Orbital metastasis from hepatocellular carcinoma revealed by sudden exophthalmos. Issue 5 (12th May 2021) - Baldovin, Maria; Saratziotis, Athanasios; Zanotti, Claudia; Emanuelli, Enzo
Abstract : Orbital metastases represent a rare condition and only 33 cases of metastases from hepatocellular carcinoma (HCC), usually revealed by slowly progressive exophthalmos, have been described in the literature. A 62-year-old man affected by HCC reported a sudden left exophthalmos and amaurosis. A cranial CT scan revealed pathological tissue occupying the superior portion of the orbit. During endoscopic decompression of the optic nerve, an active venous intraorbital haemorrhage was noted. Following angiography, permanent occlusion was performed on a neoforming circulus fed by ramification of the anterior deep temporal artery, anterior ramification of the superficial temporal artery and sphenoidal ramification of the medial meningeal artery. A percutaneous incisional orbital biopsy showed features of metastatic foci of HCC. This is the first description of orbital metastasis from HCC revealed by a sudden exophthalmos.